Comparative Study of Antivirus Adoption Rates on Smartphone-Based Operating Systems - Christinne M. T. P. Subagyo, Mersy. E. L. Sumangkut, Yunitha R. Sumarandak (International Journal of Information Technology and Education, 2022)
Anti-Virus development is growing rapidly. Some are paid and some are free. With the increasing number of Anti-Virus applications, smartphone users are faced with several choices of Anti-Virus applications. Not all smartphone users know how to work and the advantages and disadvantages of each Anti-Virus. The purpose of this study is to determine the advantages and disadvantages of 360 Security and CM Security. The benefit of this research is that it makes it easier for smartphone users to choose the right Anti-Virus application on their respective smartphones. This research will use interview, observation, analysis and design methods. The results of this study are data that can be used by smartphone users as a reference and comparison of 360 Security and CM Security.